Airway management with novel intubating laryngeal tubes has no influence on cerebral oxygenation in cardiac surgery patients: A prospective observational study - Kriege, Marc; Rissel, René; Heid, Florian; Ott, Thomas; Beyrouti, Hazem El; Hotz, Eric (Frontiers in Anesthesiology, 2022)
Background: A laryngeal tube is often used as an alternative to intubation with direct laryngoscopy during cardiopulmonary resuscitation. However, in a study with piglets undergoing simulated cardiac arrest, reduced carotid artery blood flow was associated with the insertion of different supraglottic airway devices, such as a laryngeal tube. Limited by its construction, secondary tracheal intubation through a laryngeal tube was difficult or impossible in contrast to a second generation laryngeal mask. The new disposable intubating laryngeal tube with suction (iLTS-D®) seems to facilitate tracheal intubation. We hypothesized that iLTS-D, when inflated to the recommended air volume, does not reduce cerebral oxygenation in patients with cardiovascular diseases undergoing elective cardiac surgery. Methods: This single-center prospective, controlled observational study was approved by the local ethics committee (Ethical Committee N° 2018-13716). Forty adult patients undergoing elective cardiac surgery requiring tracheal intubation were included in this study. The exclusion criteria were age < 18 years and a high risk of aspiration, inability to consent, height less than 155 cm, or pregnancy. Prior to insufflation and deflation of the cuffs, we performed cerebral oximetry via near-infrared spectroscopy. The primary outcome was a significant reduction in NIRS in the context of the preinduction baseline value after inflation of the cuffs with the recommended air volume, defined as a ≥ 25% decrease from baseline or an absolute value ≤ 50%. The secondary endpoints were differences in time points, insertion success rates, and complications. Results: There was no significant reduction in cerebral oximetry after inflation with the recommended cuff volume and an initially measured cuff pressure of > 120 cmH2O. Overall, tracheal intubation was achieved in a median of 20 s [interquartile range 15-23 s] and enabled sufficient ventilation and tracheal intubation through the iLTS-D in all patients. Traces of blood on the cuffs (after removing the iLTS-D) and a sore throat (evaluated 2 h after removing the tracheal tube) were observed in one patient. Conclusion: Our results showed no association between the insertion of the iLTS-D and reduced cerebral oxygenation in patients undergoing elective cardiac surgery. TRIAL REGISTRATION ClinicalTrials.gov, NCT03942809